2020
DOI: 10.1038/s41598-020-74617-5
|View full text |Cite
|
Sign up to set email alerts
|

HFD-induced hepatic lipid accumulation and inflammation are decreased in Factor D deficient mouse

Abstract: Excessive intake of fat causes accumulation of fat in liver, leading to non-alcoholic fatty liver disease (NAFLD). High-fat diet (HFD) upregulates the expression of Factor D, a complement pathway component, in the liver of mice. However, the functions of Factor D in liver are not well known. Therefore, the current study investigated the relationship between Factor D and hepatic lipid accumulation using CRISPR/Cas9-mediated Factor D knockout (FD-KO) mice. Factor D deficiency downregulated expression of genes re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
41
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(47 citation statements)
references
References 40 publications
5
41
0
1
Order By: Relevance
“…If researchers select this model, they can save a lot of time on NAFLD research. Many studies using NAFLD models have reported requiring long-term feeding periods of 8 to 12 or more weeks [6][7][8][9][10][11][12] to establish the model, which means severe time loss. On the other hand, this model progresses in pathology faster than normal HFD even though it is able to be established faster, so if researchers want to develop a drug with this model, they may need a stronger efficacy.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…If researchers select this model, they can save a lot of time on NAFLD research. Many studies using NAFLD models have reported requiring long-term feeding periods of 8 to 12 or more weeks [6][7][8][9][10][11][12] to establish the model, which means severe time loss. On the other hand, this model progresses in pathology faster than normal HFD even though it is able to be established faster, so if researchers want to develop a drug with this model, they may need a stronger efficacy.…”
Section: Discussionmentioning
confidence: 99%
“…There are many studies using animal models of NAFLD to develop new treatments and to investigate its molecular mechanisms. In general, the NAFLD model is created by feeding an unbalanced diet, such as a high-fat diet (HFD) [6][7][8], a high-fat high-sucrose diet (HS-HFD) [9,10], or a high-fat, high-cholesterol diet [11,12]. Moreover, NASH models including fibrosis and steatohepatitis have made using a choline-deficient, L-amino acid-defined, high-fat diet (CDAHFD) [13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, He et al found out that the phenotypic switch in adipose tissue from anti-inflammatory to pro-inflammatory macrophages is detected after 5 weeks on HFD, while metabolic inflammation is noted after 9 weeks [ 201 ]. An overall increase of pro-inflammatory cytokines such as TNF-α, IL-6, leptin and TGFβ1 is detected in the liver of HFD-fed mice for 17 weeks [ 202 ] and up to 40 weeks [ 200 ]. Moreover, other markers, such as MCP-1, PAI-1 and CCL2 are increased in adipose tissue of mice on HFD for 9 weeks [ 176 ] or up to 17 weeks [ 202 ].…”
Section: Diet Inflammation and Gut Microbiota In T2dm Modelsmentioning
confidence: 99%
“…An overall increase of pro-inflammatory cytokines such as TNF-α, IL-6, leptin and TGFβ1 is detected in the liver of HFD-fed mice for 17 weeks [ 202 ] and up to 40 weeks [ 200 ]. Moreover, other markers, such as MCP-1, PAI-1 and CCL2 are increased in adipose tissue of mice on HFD for 9 weeks [ 176 ] or up to 17 weeks [ 202 ].…”
Section: Diet Inflammation and Gut Microbiota In T2dm Modelsmentioning
confidence: 99%